Entrapment of micro-sized zeolites in porous hydrogels: Strategy to overcome drawbacks of zeolite particles and beads for adsorption of ammonium ions - Putra, Rio Nugraha; Lee, Young Haeng (Pergamon Press Ltd., 2020)
We have demonstrated that the entrapment of micro-sized zeolite particles (ZPs) in porous hydrogels is a promising strategy toward overcoming several drawbacks of ZPs and zeolite beads (ZBs) for adsorption of ammonium ions. The polyvinyl alcohol (PVA)-alginate-ZPs (PAZ) composite hydrogel beads with the same size as that of ZBs were prepared by physically entrapping the ZPs. On the basis of structural characterization results, the entrapped ZPs are well distributed with minimal agglomeration in the highly permeable and porous hydrogels. Unlike the ZPs, the PAZ hydrogels had good settleability and showed no significant further agglomeration of the entrapped ZPs even under high zeolite dosage conditions. Due to still high accessible surface area of the entrapped ZPs in the hydrogel, the maximum ammonium adsorption capacities of PAZ hydrogels from Langmuir isotherm were 3.4-4.3 times higher than those of ZBs. Thus, we propose that the entrapment of ZPs in highly porous hydrogel has much less adverse effects on the adsorption capacity, compared to the binder commonly used in the synthetic ZBs. Similar to the ZPs and unlike the ZBs, the ammonium adsorption process in the PAZ hydrogels was governed by chemical ion exchange mechanism and tended to be rate-limited by boundary layer diffusion and mainly intra-particle diffusion. Owing to the above-mentioned key features toward overcoming drawbacks of both the ZPs and the ZBs, the PAZ hydrogels have great potential as promising alternative zeolite-type adsorbents for a broad range of industrial applications in water purification and wastewater treatment.